2016
DOI: 10.1177/0018720816639418
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Air Traffic Controller Workload

Abstract: Sources that generate trajectory uncertainty, as well as their interaction effects with dynamic complexity metrics, should be acknowledged in workload prediction models to increase the predictive power of these models. Implications for future air traffic management operations as envisioned by SESAR and NextGen are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Radio communication between ATCo's and pilots represents a major contribution to the total task load, besides monitoring the traffic on the radar display (traffic count n) for anticipating possible separation conflicts (Manning et al 2001;Averty et al 2004;Djokic et al 2010;Corver et al 2016). Because communication (task) load under nominal conditions increases with traffic count, it seemed appropriate to use a one-dimensional WL measure for the experiment.…”
Section: Experimental Design and Workload Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Radio communication between ATCo's and pilots represents a major contribution to the total task load, besides monitoring the traffic on the radar display (traffic count n) for anticipating possible separation conflicts (Manning et al 2001;Averty et al 2004;Djokic et al 2010;Corver et al 2016). Because communication (task) load under nominal conditions increases with traffic count, it seemed appropriate to use a one-dimensional WL measure for the experiment.…”
Section: Experimental Design and Workload Assessmentmentioning
confidence: 99%
“…They took into account changing task priorities for WL management and strategies of operators, and emphasized traffic density as indirect WL predictor due to task demands such as identifying, monitoring, and instructing aircraft (AC) via radio communication. Corver et al showed (Corver et al 2016) that traffic conflict, moderated by trajectory uncertainty, mediates the positive effect of traffic density on WL. The specific question of ATC complexity as WL driver was investigated, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As the development of 4D trajectory operation, Zohrevandi et al (2016) designed numbers of scenarios to measure how the level of 4D equipped affect controllers' task load in terminal and en route sectors. Corver et al (2016) studies how trajectory uncertainties impact controllers' workload under various traffic density and conflict situations. This line of research, despite the fresh perspective on the relationship between traffic flow and cognitive measures, are inadequate to analyze the evolutionary dynamics of "human-flow" and the mechanisms through which they interact.…”
Section: Introductionmentioning
confidence: 99%